The English National Low Rectal Cancer Development Programme: key messages and future perspectives. (March 2014) - Moran, B. J.; Holm, T.; Brannagan, G.; Chave, H.; Quirke, P.; West, N.; Brown, G.; Glynne‐Jones, R.; Sebag‐Montefiore, D.; Cunningham, C.; Janjua, A. Z.; Battersby, N. J.; et al.
Abstract Aim Adenocarcinoma of the lower rectum is clinically challenging because of the need to choose between a wide excision to achieve oncological clearance, on the one hand, and sphincter conservation to maintain anal function, on the other. The English National Low Rectal Cancer Development Programme (LOREC) was developed under the auspices of the Association of Coloproctology of Great Britain and Ireland and the English National Cancer Action Team to improve the outcome of low rectal cancer in England. Method LOREC was initiated focusing on preoperative imaging, selective neoadjuvant therapy, optimal surgical treatment and detailed pathological assessment of the excised specimen. Its key elements were 1‐day multidisciplinary team (MDT) workshops, cadaveric surgical training, surgical mentoring, pathological audit and radiological workshops. Results Overall, 147 (89.6%) of 164 MDTs from 151 National Health Service (NHS) Trusts (some with two MDTs) in England participated in 15 workshops in Basingstoke or Leeds. In addition, 112 surgeons attended a 1‐day cadaveric training programme in Bristol, Newcastle or Nottingham, with the main focus on extralevator abdominoperineal excision and pelvic reconstruction, with input from anatomists and from colorectal and plastic surgeons. Conclusion Optimal staging, selective preoperative chemoradiotherapy and precise surgery were considered as crucial to improve the outcome for patients with low rectal cancer.